Energy efficiency of a flat-plate solar collector using thermally treated graphene-based nanofluids: Experimental study - Alawi, O.A. (SAGE Publications Ltd, 2020)
A covalent functionalization approach was utilized for the preparation of highly dispersed pentaethylene glycol-thermally treated graphene-water as the absorbing material inside a flat-plate solar collector. Four mass fractions of nanofluids were prepared (0.025, 0.05, 0.075, and 0.1 wt pentaethylene glycol-thermally treated graphene-water). Graphene nanoparticles were characterized by energy dispersive X-ray analysis with a scanning electron microscope. Measurements of the thermophysical properties were subsequently carried out for the nanosuspensions. The raw investigation data were collected from an indoor flat-plate solar collector test setup. The experimental procedure included different sets of variables such as input temperatures of 303, 313, and 323 K; fluid mass flow rate of 0.00833, 0.01667, and 0.025 kg sâ1; and heat flow density of 500, 750, and 1000 W mâ2. The thermophysical tests of pentaethylene glycol-thermally treated graphene-water nanofluids showed a proportional increase against weight concentrations, while the specific heat power was reduced. The tests showed an increment in energy efficiency by increasing the fluid mass flow rate and heat input. By comparison, the thermal efficiency decreased with the increasing temperature of the fluid supply. Relative to the base fluid, the energy efficiency of pentaethylene glycol-thermally treated graphene/water-based flat-plate solar collector increased to 10.6, 11, and 13.1 at the three fluid mass flow rates. In conclusion, an exponential form was used to derive the thermal effectiveness of flat-plate solar collector based on the experimental data. Â© The Author(s) 2020.